Reducing the raw material usage for room temperature infusible and polymerisable thermoplastic CFRPs through reuse of recycled waste matrix material. (1st July 2021) - Gebhardt, Magnus; Manolakis, Ioannis; Chatterjee, Atasi; Kalinka, Gerhard; Deubener, Joachim; Pfnür, Herbert; Chakraborty, Souvik; Meiners, Dieter
Abstract: In this work, a closed loop recycling process is investigated, which allows polymerised bulk thermoplastic matrix (Elium 150) from production waste (also referred to as recyclate) to be reused as additive in composite manufacturing by vacuum assisted resin infusion (VARI) of virgin Elium 150 monomer. It is shown that this process can save up to 7.5 wt% of virgin material usage in each processing cycle. At the same time, the thermal stability and stiffness of the composite increases with the proportion of recyclate introduced. Contemporarily, the shear and bending properties have also been observed to improve. Gel permeation chromatography (GPC) showed that the changes observed are due to an increase in molecular weight with the recyclate content. In particular, a correlation between the molecular weight and the shear properties of the composite was discovered using single fibre push-out tests.